Formación de los docentes previo al servicio en el cantón Pangua - Fauta Ramos, Silvia Liliana (2017)
The changes which are required and are proposed with the purpose of improve the society life quality in topics related to education, should analyze the educative structure and its efficiency, for that reason is necessary start for the formative stage in this case of the teachers, analyze the reality, determine causes and consequences about possible deficiencies and success, in order to in the median or long term propose integral projects, that effectively determine the achievement of educative standards, thus, is posed to achieve as a general objective of this research to diagnose the formation of the teachers previous to the service through the performance of a field research, to generate alternatives of improvement in the academic process of the Basic Education career.¿ In which way it affects the formation of the teachers in their performance previous to the service?, for which we will work in base to the Deductive method, in the structure of the theoretical framework, the Inductive, in order to do the analysis and interpretation of results, the Analytic method in the field work so the systematization of the bibliographic information, the research technics like the survey which will be applied to the teachers and managers of the Educative System Pangua that permit us to obtain accurate information of the required elements as a part of the research, with in the principal results which we hope will be framed in the feasibility of the development of a diagnostic of the formation of the teachers previous to the service….